Open-cell porous aluminium for heat transfer applications - Njoku, Romanus Egwuonwu (2017)
Open- cell porous aluminium shows great potential for use in energy storage systems and as filters in metallic and chemical industries due to their good thermal and fluid transport properties. In this work, open- cell porous aluminium structures were produced by the infiltration of liquid aluminium through the pore spaces between loose compacts of sodium chloride beads of different particle sizes and pressure conditions. The cell/pore window size, relative density and porosity of the porous aluminium materials were varied by using sodium chloride beads of different sizes and packing densities and by producing samples at different infiltration pressures. The samples were characterised by optical microscopy, scanning electron microscopy, micro- computed tomography and the thermal conductivity and electrical resistivity of the samples were determined using a C- therm analyser and an ohmmeter. A test rig consisting of a heat source, K- type thermocouples, infrared camera, data logging instruments and computers equipped with “Altair” software was used to investigate the thermal response of both empty and PCM- filled porous aluminium samples while a permeameter consisting of a flask and measuring beaker was used for measuring the permeability of the porous samples. Microscopic and tomographic analyses reveal that the structure of the porous materials consists of near spherical cells, randomly dispersed within aluminium matrix and which are interconnected by pore windows and that the pore window diameter of the porous aluminium structures increases as the infiltration pressure is decreased while the cells replicate the shape and size of sodium chloride beads from which they are manufactured.. Thermal analyses show that the thermal conductivity of the porous samples varies as a power of the relative density of the porous material and that a Scaling function: kf = ks〖(_f/_s )〗^nbased on percolation theory with n = 1.89 and the Ashby model: kf = ks(_f/_s ) with  = 0.42 best fit the experimental data for thermal conductivity of the porous aluminium structures. Heat transfer performance evaluation of the open- cell porous aluminium structures show that at constant relative density and for the range of relative density of the porous structures (0.35- 0.40), the response of the porous aluminium samples to heat increases with the window diameter and relative density of the open- cell porous aluminium structures and that the time for stearic acid PCM infiltrated in the open- cell porous aluminium structures to attain 70 oC is up to 13 times faster than for pure stearic acid wax to attain the same temperature. Permeability test shows that the permeability of the porous aluminium structures varies as a power of the window diameter of the porous materials and that the Nusselt and heat transfer coefficient of the porous aluminium structures increase exponentially with the permeability of the porous materials.